EKSPERIMENTASI MODEL PROBLEM BASED LEARNING (PBL) DENGAN WRITING ACTIVITIES DAN MODEL CREATIVE PROBLEM SOLVING (CPS) PADA MATERI BARISAN DAN DERET DITINJAU DARI KREATIVITAS BELAJAR MATEMATIKA SISWA KELAS X SMK SE-KOTA TEGAL TAHUN AJARAN 2014/2015 - Yuliana, Tri; Kusmayadi, Tri Atmojo; Sujadi, Imam (Jurnal Pembelajaran Matematika, 2016)
Abstract: Problem solving ability was main objective in this mathematic’s learning. So this research intends to know the students’ achievement of mathematics which was better (1) students were taught by Problem Based Learning (PBL) with Writing Activities (WA), students were taught by Creative Problem Solving (CPS) or students were taught by Direct Learning, (2) students with high creativity, students with medium creativity, or srudents with low creativity, (3) in each category creativities, the students’ achievement of mathematics was better among the students were learnt by PBL with WA, CPS or direct learning models (4) in each model, the students’ achievement of mathematics was better among the students with high creativity, students with medium creativity, students with low creativity. This research used a quasi-experimental research with the population of tenth grade of High Schools in Tegal city in the Academic Year of 2014/2015. The sampling technique used stratified cluster random sampling and three schools were selected namely SMK N 1 Tegal, SMK N 2 Tegal, and SMK N 3 Tegal. Two-way variance’ analysis was used to test the hypothesis, followed by Scheffe’ technique. The results of analysis were as follows. (1) The students’ achievement by PBL with WA were better than by CPS and direct learning. The students’ achievement by CPS were better than by direct learning. (2) The students’ achievement with high creativities were better than with medium and low creativity. The students’ achievement with medium creativity were better than with low creativity. (3) In every category of creativities (high, medium and low), the students’ achievement by PBL with writing activities were better than CPS and direct learning. The students’ achievement by CPS were better than direct learning. (4) In every model of learnings (PBL with WA, CPS, and direct learning), the students’ achievement with high creativity were better than medium creativity and low creativity. The students’achievement with medium creativity were better than with low creativity.Keywords: Problem Based Learning with Writing Activities, Creative Problem Solving, Creativities, achievement of mathematics.